Baduy Community Education Perennialism - Mualimah, Eka Nurul; Syihabuddin, Syihabuddin; Sastromiharjo, Andoyo (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to determine the education pattern of the Baduy community. The research method used is a descriptive qualitative research method and seeks the necessary data by direct observation in the Baduy Tribe and conducting interviews with the traditional leaders of the Baduy Community. The elements of perennialism found in the education pattern of the Baduy community are basic knowledge that is eternal and universal, upholding cultural heritage, parents and communities having a role in guiding cultural values to the younger generation, character education and experience-based learning in upholding traditional values. and cultural heritage.